Chemically Stable Semitransparent Perovskite Solar Cells with High Hydrogen Generation Rates Based on Photovoltaic–Photoelectrochemical Tandem Cells. Issue 5 (28th January 2022) - Ban, Hayeon; Park, Jaemin; Yun, Juwon; Ma, Sunihl; Jang, Gyumin; Goh, Sukyoung; Lee, Chan Uk; Lee, Junwoo; Moon, Jooho
Abstract : Photovoltaic (PV)‐assisted photoelectrochemical (PEC) tandem cells with elevated hydrogen (H2 ) production rates are a practical approach for carbon‐dioxide‐free, green H2 production. A semitransparent single‐cell‐based wide‐bandgap perovskite solar cell (PSC) coupled with an Si photocathode provides sufficient potential for H2 generation when combined with a sulfate oxidation reaction. While energetically favorable ZnO as an electron transport layer (ETL) increases the V OC to 1.19 V for mixed‐halide perovskite, phase decomposition is induced when Br ions contacted the ZnO ETL. The SnO2 interlayer shows improved passivation, superior operational stability, and excellent performance among the various atomic layer deposited metal oxides tested. Furthermore, the resulting semitransparent PSC demonstrates reproducibility of its enhanced PV parameters (i.e., V OC 1.17 ± 0.01 V, FF = 76.78 ± 1.39%, and PCE = 11.95 ± 1.13%) due to better interface quality. The precise calculation of light absorption from both PV and Si for the overall tandem device leads to optimized light harvesting in the top and bottom electrodes, maximizing H2 production. Overall, the PV‐PEC device incorporated with a chemically stable semitransparent top PSC and bottom Si photocathode allows to accomplish stable H2 production at 11.1 mA cm −2 under unbiased conditions. Abstract : A hydrogen production system involving ZnO ETL‐based semitransparent PSC and Si photocathode combined with SOR is presented. The device operational stability for ZnO ETL‐based PSC is sufficiently extended by introducing an ALD‐derived SnO2 interlayer. The well‐designed PV‐PEC tandem cell demonstrates a remarkable hydrogen‐generating photocurrent density of 11.1 mA cm −2 .